2022
DOI: 10.1016/j.acra.2021.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of Gender Discrimination and Sexual Harassment in the Radiology Workplace: A Survey

Abstract: Rationale and Objectives: Our objectives were (1) to determine the extent to which gender discrimination and sexual harassment are experienced by female radiologists and trainees; (2) to examine whether experiencing harassment or discrimination influences perceptions of gender parity; and (3) to explore whether the existence of either formal institutional policies or the number of women in the workplace and/or in leadership positions influences perceptions of having achieved gender equity.Materials and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 17 publications
1
10
0
1
Order By: Relevance
“…Beyond blocked opportunities and reduced wages, the position of a level of authority is also accompanied by an unsupportive environment which makes it difficult to work effectively ( 31 ). GD has been recently condemned publicly which is seen in all fields of medicine to be experienced more by women ( 32 , 33 ), however, surgical fields pose a different challenge due to the male stereotype deeply rooted in the minds of patients, nursing staff and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond blocked opportunities and reduced wages, the position of a level of authority is also accompanied by an unsupportive environment which makes it difficult to work effectively ( 31 ). GD has been recently condemned publicly which is seen in all fields of medicine to be experienced more by women ( 32 , 33 ), however, surgical fields pose a different challenge due to the male stereotype deeply rooted in the minds of patients, nursing staff and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-six percent of women physicians report harassment in their career [ 20 ] and 50% of female faculty and students experience sexual harassment in academia [ 21 ]. A recent study among female radiologists found that 60% of respondents reported being a victim of sexual harassment and 84% a victim of gender discrimination in the workplace [ 22 ].…”
Section: Why Is This An Important Topic?mentioning
confidence: 99%
“…Perempuan-perempuan hampir di semua sektor sejauh ini menerima berbagai macam pola diskriminasi (Fattore et al, 2020;SteelFisher et al, 2019), baik di dalam keluarga (Cerrato & Cifre, 2018;Sullivan, 2019), di ruang publik (Jones et al, 2018), di ruang kerja (Bastian et al, 2019;Hardies et al, 2021;Kim et al, 2020;Manzi, 2019;Pitot et al, 2022), pendidikan (Assoumou-ella, 2019;Baliamoune-Lutz & McGillivray, 2015;Cooray & Potrafke, 2011;Karoui & Feki, 2018;Zeng et al, 2014) dan sektor-sektor lainnya. Keadaan ini banyak dipengaruhi oleh pengarusutamaan gender yang tidak memposisikan perempuan sebagaimana mestinya dan mengabaikan nilai-nilai kesetaraan.…”
Section: Potensi Ekonomi Perempuanunclassified